Institutional and legal framework for the functioning of the EU tax systems - Grytsyshen, Dymytrii; Abramova, Iryna; Islamli, Jeyhun (Public Policy and Accounting, 2025)
The study focuses on the institutional and legal framework for the functioning of the tax systems of the European Union countries. The aim of the study is to provide a theoretical substantiation of the institutional and legal framework for the functioning of the EU taxation system. It is argued that taxation systems in the European Union are of key importance for financing public expenditures, maintaining social stability and economic development. The tax system of each member state, although based on common European principles, is developed on the basis of national priorities and economic conditions. It is substantiated that the institutional framework of taxation ensures the effective functioning of the tax system through a number of mechanisms: the legislative framework, legal norms, principles of fairness, transparency and responsibility. The author emphasizes that the Fiscalis program plays an important role in ensuring cooperation between the tax authorities of the EU Member States. Regulation (EU) 2021/847103 was a key document that updated the previous regulation and proposed new mechanisms to improve tax administration and cooperation between tax authorities. The author emphasizes that the effective functioning of the EU tax systems depends on harmonization of legislation, international cooperation, efficient tax administration and a reliable judicial system, which ensures the financial stability of the States and promotes economic growth and social development.